The Educational Staff of the Penitentiary in the Moral Correction and Education of Convicted Persons Types of Pedagogical Skills - Khotamov Shukrat Nasirovich (Zien Journals, 2022)
This article analyzes the types of pedagogical skills necessary for educators who are directly involved in the moral correction and education of convicts in penal institutions. Also, the specific features of the operation of penal institutions and the pedagogical requirements imposed on the employee of the penal institution based on these characteristics are highlighted.
Keywords: pedagogic worker of a penal institution; expressive abilities; level of knowledge; internal culture